VELIZIA INCONSTANS CESARI & HÜNICKEN (GYMNOSPERMAE) EN LA FORMACION CERRO AGUA NEGRA (PALEOZOICO SUPERIOR), SAN JUAN, REPUBLICA ARGENTINA (Ameghiniana, 2013)
A specimen of Velizia inconstants Césari & Hünicken (gymnospermous leaf) found in the Cerro Agua Negra Formation, Río Blanco Basin, Argentina, extends the geographic range of the taxon to another sedimentary basin.